The construction of the training process of young weight lifters 12–13 years old during a one-year macrocycle, taking into account the specific biological cycle - Канунова, Людмила; Джим, Віктор (Slobozhanskyi Herald of Science and Sport, 2019)
Liudmyla Kanunova & Viktor Dzhym Purpose: to consider the question of building the training process of young weight lifters of 12–13 years during a one-year macrocycle, taking into account the peculiarities of a specific biological cycle. Material & Methods: the methods of theoretical analysis and generalization of scientific information, system analysis are used in the work. Results: modern approaches to constructing the training process of young weight lifters of 12–13 years are presented, a detailed structure of the construction of a one-year macrocycle taking into account the CMC phases is presented. Conclusions: it was determined that for young athletes involved in kettlebell lifting, it is necessary to carry out a detailed load distribution in accordance with the phases of the CMC during a one-year macrocycle, and it is necessary to take into account loads in basic and competitive mesocycles.